TANGGUNG JAWAB PT. UNIVERSAL PHARMACEUTICAL INDUSTRIES ATAS OBAT UNIBEBI COUGH SYRUP BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 PERLINDUNGAN KONSUMEN - Tio Rae, Fabio; Kerti, N.G.N. Renti Maharaini (Tribuere, 2023)
The incident of hundreds of children in Indonesia experiencing Acute Kidney Failure at the end of 2022 was caused by the distribution of syrup drugs containing Ethylene Glycol (EG) and Diethylene Glycol (DEG) contamination, one of which was the drug Unibebi Cough Syrup produced by PT. Universal Pharmaceutical Industries. In particular, business actors are prohibited from trading defective and contaminated pharmaceutical preparations. This is because business actors are obliged to guarantee that the goods produced/traded meet the applicable standard criteria. So that. Consumers' rights to security, comfort and safety in consuming goods traded by business actors can be fulfilled. Therefore, it is necessary to know how to regulate good standards for pharmaceutical preparations based on a consumer protection perspective and how to restore the rights of consumers who have been harmed. This type of normative research uses laws and related legal theories. From a consumer protection perspective, business actors in producing pharmaceutical preparations are regulated to be guided by the Indonesian Pharmacopoeia and Good Medicine Manufacturing Practices (CPOB) as standards for good pharmaceutical preparations. Consumers who have been harmed can take legal action through class action lawsuits as a form of effort to restore their rights that have been violated by business actors